Delhi Development Report Planning Commission Government of India New Delhi - Planning Commission (Planning Commission, 2007)
Development and devastation has been the destiny of Delhi1 during the best part of the last millennium. Many a time, it was re-built and re-christened with a new magnificence and many a time, it was depredated and destroyed by invaders. The anguish expressed by Mir in the cited couplet was only one such occasion when he fled from Delhi and had to introduce himself to a new audience in another seat of culture—Lucknow—in the middle of eighteenth century following the invasion of Nadir Shah. But it was not the last time that this happened to Delhi.
Planning Commission Government of India
Planning Commission Government of India